THE EFFECTIVENESS OF AUDIO-VISUAL MEDIA TO IMPROVE STUDENTS’ SPEAKING ABILITY IN MADRASAH TSANAWIYAH (MTs) MA’ARIF MIFTAHUL HUDA LEMPUYANG ANJATAN INDRAMAYU - Supriyani Supriyani; Mar’atus Sholikhah; Kunah Kunah (STIBA IEC JAKARTA, 2023)
This study is an attempt to determine the effect of using audio-visual media on improving student learning abilities at MTs Ma’arif Miftahul Huda Lempuyang Anjatan Indramayu. This research is to answer the questions: (1) How is the students’ speaking ability in MTs Ma’arif Miftahul Huda Lempuyang Anjatan Indramayu? (2) How is the fluency of students’ speaking ability in MTs Ma’arif Miftahul Huda Lempuyang Anjatan Indramayu? (3) Hoe effective is audio-visual media to improve students’ speaking ability in MTs Ma’arif Miftahul Huda Lempuyang Anjatan Indramayu? This study used quantitative method.The data collection method used the pre-test method, the treatment method and the post-test method. The population in this study was 251 and a sample of 71 students were taken from grade 8. The results of this study showed the average score of students was 55,5 after being given treatment, there was a significant change in the improvement, the average score of students was 71. Improved learning outcome after using audio-visual media by 15,5 %. From this research, it can be concluded that there is effectiveness in using audio-visual media to improve students’ speaking ability